Endoscopic endonasal dacryocystorhinostomy-an experience in a tertiary care hospital - Gujrathi, Atishkumar B.; Kamble, Paritosh A.; Khadkekar, Shashin; Gadpayale, Nishikant; Paikrao, Yogesh; Kurande, Harshada; Rathod, Indutai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Dacryocystorhinostomy is a surgical procedure by which the lacrimal flow is diverted into the nasal cavity by making an opening in the lacrimal sac when the nasolacrimal duct gets blocked. The operation can be carried out using either an external or endonasal surgical approach. Methods: This is a clinical observational study done on 50 patients with chronic dacryocystitis with obstruction at the level of sac or nasolacrimal duct. This study was conducted at Dr. Shankarrao Chavan government medical college, Nanded, during the period of 2 years (2018-2020). Patients were evaluated and operated for endoscopic endonasal dacryocystorhinostomy. Results: The mean age of studied cases was 33.92±12.13 years. The M:F ratio was 0.78. Epiphora was the predominant complaint in all cases 100%. Swelling of lacrimal sac was present in 24% cases and Pain on affected side was present in 18% cases. 6% patients had fistula on the side of block. 12% patients had mucocele and 14% patients had pyocele on the affected side. Left and right side was involved in 54% and 40% cases respectively. The disease presented bilaterally in 06% cases. 80% patients had no complications after endonasal endoscopic dacryocystorhinostomy (EEDCR) surgery. Rate of surgical success was 92%. Conclusions: Nasolacrimal duct obstruction is more common among females and in middle aged persons. EEDCR is treatment which provides patients relief from the symptoms without any scar and also preserves nasolacrimal pump system with high success rate. It may prove better surgical technique in chronic dacryocystitis.